Strategic issues in management accounting (Hampshire : Workhouse Limited, 1995)
Covers strategic management accounting investment appraisal and TQM. Using real and hypothetical case studies Prof. Richard Wilson explains the importance of strategic management accounting (SMA) as a means of measuring relative performance, establishing competitive position and devising corporate strategy.
Copy available in DVD format.x
Keywords: Managerial accounting; Total quality management -- Case studies